The role of CLAVATA signalling in the negative regulation of mycorrhizal colonization and nitrogen response of tomato. (13th November 2020) - Wang, Chenglei; Velandia, Karen; Kwon, Choon-Tak; Wulf, Kate E; Nichols, David S; Reid, James B; Foo, Eloise
Abstract : We describe the role of CLV signalling elements in the negative regulation of arbuscular mycorrhizal symbioses in tomato, including influencing nitrate but not phosphate suppression of mycorrhizal colonization. Abstract: Plants form mutualistic nutrient-acquiring symbioses with microbes, including arbuscular mycorrhizal fungi. The formation of these symbioses is costly, and plants employ a negative feedback loop termed autoregulation of mycorrhizae (AOM) to limit formation of arbuscular mycorrhizae (AM). We provide evidence for the role of one leucine-rich repeat receptor-like kinase (FAB), a hydroxyproline O -arabinosyltransferase enzyme (FIN), and additional evidence for one receptor-like protein ( Sl CLV2) in the negative regulation of AM formation in tomato. Reciprocal grafting experiments suggest that the FAB gene acts locally in the root, while the SlCLV2 gene may act in both the root and the shoot. External nutrients including phosphate and nitrate can also strongly suppress AM formation. We found that FAB and FIN are required for nitrate suppression of AM but are not required for the powerful suppression of AM colonization by phosphate. This parallels some of the roles of legume homologues in the autoregulation of the more recently evolved symbioses with nitrogen-fixing bacteria leading to nodulation. This deep homology in the symbiotic role of these genes suggests that in addition to the early signalling events that lead to the establishment of AM and nodulation, the autoregulation pathway might also be considered part of the common symbiotic toolkit that enabled plants to form beneficial symbioses.